PENGARUH MANAJEMEN PEMBIAYAAN TERHADAP KESEJAHTERAAN GURU DI MADRASAH - Badrudin , Badrudin; Hermawan, A. Heris; Pangestika, Annisa Nopradhina (UII Darullughah Waddawah Pasuruan, 2022)
Financing management is one of the most important elements in educational institutions because it is related to the implementation of madrasah activities. The problem that arises in financing management is that financing has not been managed properly so that there are still many teachers who are less prosperous. Therefore, as the manager of madrasah financing management is required to be more optimal and pay attention to financing management and improve teacher welfare. The objectives of this study were to determine: 1) financial management at Madrasah Tsanawiyah Al-Hidayah Sukatani, Depok City; 2) the welfare of teachers at Madrasah Tsanawiyah Al-Hidayah Sukatani, Depok City; 3) the influence of financing management on the welfare of teachers in Madrasah Tsanawiyah Al-Hidayah Sukatani, Depok City. This research uses a quantitative approach, with a descriptive verification method. The data in this study were obtained through distributing questionnaires (questionnaires). Data analysis techniques in this study used research instrument tests (validity and reliability), normality test, linearity test, heteroscedasticity test, simple linear regregi, T test and coefficient of determination. This study has a framework in which financing management has four indicators, including financing planning, financing implementation, financing supervision, and financing accountability. Meanwhile, teacher welfare has three indicators, including understanding the rights that must be received, additional income, and the suitability of the rights received. The results of this study indicate that: 1) the reality of financing management at Madrasah Tsanawiyah Al-Hidayah Sukatani, Depok City is in the medium category, based on the assessment results of 33 respondents, namely 57%. 2) the reality of the welfare of teachers at Madrasah Tsanawiyah Al-Hidayah Sukatani, Depok City, is in the medium category from the results of the assessment of 33 respondents, namely 85%. 3) and there is a significant influence between the variable x (management of financing) on ​​the variable y (teacher welfare). The results of the T test show that the value of T count (3,300)> T table (2,042), which means that H0 is rejected. Then the results of the simple linear regression test show that the constant value (a) is 36.240, the regression coefficient (b) is 0.510. And the value of R Square is 0.260 and the result is 26.0%, so that the welfare of teachers is influenced by financial management, and 74.0% is influenced by other factors outside the research. Thus, it is hoped that the management of financing at Madrasah Tsanawiyah Al-Hidayah Sukatani, Depok City can be maintained and improved for the better in order to improve the welfare of teachers in madrasah.